Coordination Chemistry of the Tris(pentafluoroethyl)stannate(II) Anion, [Sn(C2F5)3]–. Issue 35 (26th August 2018) - Klösener, Johannes; Wiesemann, Markus; Neumann, Beate; Stammler, Hans‐Georg; Hoge, Berthold
Abstract : In this contribution the syntheses of transition metal complexes of the electron‐withdrawing Sn(C2 F5 )3 ligand are presented. The reaction of HSn(C2 F5 )3 with organometallics L n M–R (M = Zn, W, Mo; R = Et, Me; L = CO, Cp), metal carbonyls [Ni(CO)4 ], and [{Fe(CO)2 Cp}2 ], as well as chloro complexes such as [TiCl2 Cp2 ], furnished the corresponding stannylated compounds. The electron‐deficient Sn(C2 F5 )3 ligand significantly influences the IR spectroscopic and structural features with respect to related non‐fluorinated stannyl complexes. Abstract : The reaction of HSn(C2 F5 )3 with organometallics, metal carbonyls, as well as chloro complexes furnished the corresponding stannylated transition metal compounds. The electron‐deficient Sn(C2 F5 )3 ligand significantly influences the IR spectroscopic and structural features which distinguishes it from non‐fluorinated stannyl complexes.